Selection of yeast species for hydrocarbons and phenolic compounds degradation - Lopes, Marlene (2019)
[Excerpt] 1. Introduction. Large amounts of pollutant compounds are present in industrial effluents and, often, they are not totally degraded by physical and/or chemical methods before the discharge into the environment. Hydrocarbons and phenolic compounds are two examples of pollutants present in agro-industrial effluents, respectively in petroleum refinery effluents and olive mill wastewater (OMW). Biodegradation strategies involving microorganisms to simultaneously degrade these wastes and obtain high added-value products become an interesting approach, since the abundance of these compounds ensures the economic viability of bioprocesses while prevents major environmental problems. This work address the study of the ability of yeast species to grow on hydrocarbons and phenolic compounds as sole carbon and energy source. Moreover, the production of valuable compounds from these wastes was also assessed. [...]